Adoption and desirable characteristics of Information and Communication Technologies for urban small-scale food producers in South Africa - Alfonsi, Robert Massimo; Naidoo, Merle; Gasparatos, Alexandros (Frontiers in Sustainable Food Systems, 2024)
Small-scale food producers can benefit significantly from the adoption and effective utilization of Information and Communication Technologies (ICTs). For example, ICTs can help improve food production and access to markets, which is particularly valuable in many Sub-Saharan African countries that both urbanize rapidly but whose food systems still rely significantly on small-scale food producers. This study examines the adoption patterns and desirable characteristics of ICTs, as well as the factors influencing them, among small-scale food producers engaged in urban agriculture in South Africa. We administered 85 in-person surveys through referrals from local producers’ network in disadvantaged areas of Cape Town (n=21; Gugulethu, Philippi, Khayelitsha) and Johannesburg (n=64; Central Business District, Soweto, Orange Farm). A substantial proportion of respondents articulated the need for food-related mobile applications with functions that facilitate price comparisons, and the sharing of best practices and health advice. User-friendliness, low internet data use, and affordability were perceived as the most important characteristics for food-related mobile applications. Redundancy analysis (RDA) reveals that socioeconomic and demographic factors significantly influence the desired functionalities of food apps and their preferred activities among the respondents. Producers that are married and have more children, have higher income and education, and own larger land holdings, show very distinct patterns in terms of desirable app functions and uses for food apps. Our research underscores the need for comprehensive approaches to the development and promotion of food-related ICTs when targeting small-scale food producers. The barriers and needs identified here can help ICT developers, development agencies and policy-makers design fir-for-purpose interventions and policies to facilitate ICT adoption among urban small-scale food producers in rapidly urbanizing areas.